Evidence for adenosine mediation of atrioventricular block in the ischemic canine myocardium. - Belardinelli, L (1981)
Adenosine levels in oxygen-deprived myocardium can rise to 10- 100 microM concentrations known to cause atrioventricular (AV) conduction delay and block. We reported that the AV conduction delay and block caused by hypoxia is markedly attenuated by 10 microM aminophylline, and adenosine competitive antagonist. THe purpose of the present study was to investigate adenosine's role in ischemic AV conduction disturbances. Dogs were anesthetized and instrumented for His bundle and surface electrogram recordings. The total AV conduction time was subdivided in to atrial-His bundle (AH) and His bundle-ventricle intervals. The atrioventricular node artery (AVNA) was cannulated for selective injection of drugs in the AV node region. Adenosine (10 to 100 microgram), as a 2-ml bolus injection, rapidly produced a dose-dependent, transient increase in the AH interval; a 1,000-microgram dose caused second degree AV block. The duration of the increase in AH interval was also dose-dependent. Dipyridamole, and inhibitor of nucleoside transport, potentiated the negative dromotropic effects of adenosine, whereas aminophylline attenuated them. In some dogs, after cannulation of the AVNA, first and second degree AV block occurred spontaneously or were induced by rapid atrial pacing. Injection of the aminophylline (5 mg/kg, i.e.) or theophylline (100-1,000 microgram) into the AVNA rapidly reversed the AV blocks. Upon washout of the drugs the AV blocks recurred. We conclude that endogenously released adenosine may account for a major fraction of the AV conduction delay and block associated with impaired blood supply to the AV node, and the theophylline and aminophylline reverse the AV conduction defect by antagonizing the effects of adenosine.